PENGARUH PERCEIVED ENTERTAIMENT DAN NORMA SUBJEKTIF TERHADAP WORD OF MOUTH DENGAN KEPUASAN KONSUMEN SEBAGAI PEMEDIASI PADA KONSUMEN MOBILE SHOPPING KOTA BANDA ACEH - Ryanda Fajar, Wirdah Irawati (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2018)
Abstract: This research aims to determine the effect of perceived entertainment and subjective norms on word of mouth with consumer satisfaction as mediation in the mobile shopping consumers of the city of Banda Aceh, Aceh. This research method uses the google form as a research instrument. Saturated sampling and purposive sampling are used as sampling techniques. The PLS (Partial Least Square) analysis method is used as an analytical method to determine the effect of the variables involved. The results of this study indicate that perceived entertainment has a positive and significant effect on word of mouth, subjective norms have a positive and significant effect on word of mouth, perceived entertainment does not have a positive and insignificant effect on customer satisfaction, subjective norms have a positive and significant effect on customer satisfaction, perceived Entertainment has a negative effect on word of mouth with consumer satisfaction as mediation, and subjective norms have a positive and significant effect on word of mouth with consumer satisfaction as mediation.Keyword: Perceived Entertainment, Subjective Norms, Customer Satisfaction. Customer Loyaltiy, Word of Mouth.